A new approach to earthquake precursors distinction - Korepanov, V. E.; Dudkin, F. L. (Geofizicheskiy Zhurnal, 2012)
A lithospheric ultra low frequency (ULF) magnetic activity is recently considered as very promising candidate for application to short-time earthquake (EQ) forecasting. However the ULF lithospheric magnetic field is very weak and masked by much stronger ionospheric and magnetospheric signals. The study of pre-earthquake magnetic activity is very hard problem which consists of identification and localization of weak signal sources in seismo-hazardous area of the Earth crust. A new approach is developed to find a source of pre-EQ ULF electromagnetic activity of lithospheric origin. For separation and localization of EQ magnetic precursors the polarization ellipse technique has been developed to process the measurements data acquired from 3-component magnetometers. The method efficiency is illustrated at the example of the data from fluxgate magnetometers installed in Sichuan province. The Panzhihua earthquake with magnitude Mw 6,0 was happened in the southern part of Sichuan province on August 30, 2008 at 8:30:52 UT. The EQ hypocentre was located in point 26,28 N, 101,92 E at depth 10 km.